Implementasi Metode Utrujah dalam Program Unggulan Takhassus Tahfidz Quran di SDIT Sahabat Quran Talawi Hilir Kota Sawahlunto - Mayesta, Maia; Wardefi, Riza (Lembaga Yasin AlSys, 2025)
The Quran contains the words of Allah, which serve as a guide for Muslims in all aspects of life, as it provides instructions from Allah Swt. to direct the purpose of human life. This study aims to understand and examine the implementation of the Utrujah method in the flagship Tahfidz Quran program at SDIT Sahabat Quran Talawi Hilir, Sawahlunto City. The research uses a qualitative method with a case study approach. Data sources were gathered from 6 informants, consisting of 1 school principal, 2 Takhasus teachers, and 3 Takhasus students through interviews. All interview results were then analyzed through data reduction, data presentation, and conclusion drawing, followed by validation using technique triangulation and source triangulation. The findings of the study indicate that the implementation of the Utrujah method in the flagship Takhasus Tahfidz Quran program at SDIT Sahabat Quran is carried out through planning, implementation, and evaluation. Planning includes preparing Takhasus teachers, Takhasus students, and student learning models. The implementation of the Utrujah method is carried out in three stages: the first stage is the Pra-Alquran, which involves the introduction of hijaiyah letters, followed by the Tahsin stage, which focuses on the improvement of Quranic recitation by applying the materials learned in the Pra-Alquran stage, and concluded with the Tahfidz stage, which is the process of memorizing the Quran with correct recitation. The evaluation results show that the percentage of students achieving their targets is 90%.